CTNI-54. A SINGLE ARM PHASE II STUDY OF THE DUAL MTORC1/MTORC2 INHIBITOR VISTUSERTIB PROVIDED FOR SPORADIC PATIENTS WITH GRADE II-III MENINGIOMAS THAT RECUR OR PROGRESS AFTER SURGERY AND RADIATION. (12th November 2021) - Plotkin, Scott; Kumthekar, Priya; Wen, Patrick; Barker, Fred; Beauchamp, Roberta; Gerstner, Elizabeth; Muzikansky, Alona; Smith, Miriam; Stemmer-Rachamimov, Anat; Jordan, Justin; Ramesh, Vijaya
Abstract: Grade II/III meningiomas have increased rates of recurrence with no approved medical therapies. The historical progression-free survival at 6 months (PFS-6) is 25% with rates >35% declared of interest for drug development. NF2 gene inactivation occurs in about half of meningiomas. Based on our studies showing mTORC1 and mTORC2/SGK1 pathway activation in NF2 -deficient meningiomas and the paradoxical activation of the mTORC2/AKT pathway, we hypothesized that mTORC1/mTORC2 inhibitors would be active in meningiomas. We studied the effect of vistusertib in patients with progressive/recurrent grade II/III meningiomas (NCT03071874). Vistusertib was administered orally at 125mg twice daily on two consecutive days each week. MRIs were obtained every 56 days. Tumor size was defined as the largest cross-sectional area. Progression was defined as ≥ 25% increase in the sum of products of all measurable lesions over smallest sum observed. The primary endpoint was PFS-6. Secondary endpoints included toxicity, radiographic response, and correlative studies including immunohistochemistry for mTORC1/2 pathway activation and genetic biomarkers. Twenty-eight patients (13 female, median age 58 years, median KPS 80%) were enrolled. Median tumor size was 4.4cm; 71% were grade II and 50% harbored pathogenic NF2 variants. Four patients discontinued treatment voluntarily and 1 each withdrew for intercurrent illness and non-compliance. PFS-6 is 47% (CI, 26%-65%) and OS-12 is 72% (95%CI, 48%-86%). PFS but not OS was shorter for patients with grade 3 meningiomas; there was no difference in PFS/OS between genetic groups. Adverse events at least possibly related to vistusertib with frequency >10% include nausea, fatigue, hypophosphatemia, diarrhea, anorexia, dry mouth, hypertriglyceridemia, hypertension, vomiting, increased ALT, constipation, and weight loss. Vistusertib treatment was associated with a PFS-6 rate exceeding the target of 35% for recurrent high-grade meningioma. Adverse events were tolerable in this patient population. These data support the continued development of mTORC1/2 inhibitors in this setting.